The potential mechanism of huazhuojiedu decoction in the treatment of ulcerative colitis based on network pharmacology and experimental validation - Jia, Xuemei; Li, Ze; Guo, Yuxi; Ma, Hongyu; Wang, Jie; Xue, Yucong; Li, Bolin; Cai, Yanru; Yang, Qian (Frontiers in Pharmacology, 2022)
Huazhuojiedu decoction (HZJDD), a traditional Chinese medicine prescription, has been clinically proven to be an effective treatment for ulcerative colitis (UC). However, the mechanism of HZJDD in the treatment of UC remains unclear. This study combined network pharmacology with experimental validation to explore the potential mechanism of HZJDD on UC. First, the relationship network diagrams between HZJDD and UC were established based on multiple databases. Then, the HZJDD-UC intersection genes target network was constructed and Gene Ontology-Biological processes (GO-BP) analysis was performed to discover the potential pharmacological mechanism. Finally, the results of GO-BP were verified in dextran sulfate sodium salt (DSS) induced UC rats. The network pharmacology results showed that 119 active components and 146 potential targets were screened for HZJDD, and six of the top 15 biological processes belonged to inflammatory response, cellular response to hypoxia, and cellular response to lipopolysaccharide (LPS). The GO-BP results indicated that the mechanism of HZJDD treatment of UC was related to inflammation, oxidative stress, and the regulation of LPS. Animal experiments showed that HZJDD could significantly reduce the disease activity index (DAI) score, improve colon length, and effectively repair the histomorphological and micromorphological changes in DSS-induced UC rats. Moreover, HZJDD reduced the expressions of CRP, TNF-α, IL-6, LPS, IL-1β, and IL-18; down-regulated the activity of MDA; and up-regulated the activities of CAT, GSH, and SOD in DSS-induced UC rats. Furthermore, HZJDD suppressed the expression of the NLRP3/caspase-1 signaling pathway at the gene and protein levels to inhibit pyroptosis. Network pharmacology and animal experiments showed that HZJDD exerted a therapeutic effect on DSS-induced UC rats by reducing inflammation, oxidative stress, and restraining the NLRP3/caspase-1 signaling pathway to inhibit pyroptosis.